Interaction and intracellular killing of Candida albicans blastospores by human polymorphonuclear leucocytes, monocytes and monocyte-derived macrophages in aerobic and anaerobic conditions - Thompson, H L; Wilton, J M (Clinical and experimental immunology, 1992)
Polymorphonuclear leucocytes (PMN), monocytes and monocyte-derived macrophages were capable of interacting with opsonized C. albicans in both aerobic and anaerobic conditions. Superoxide anion release by these cells was inhibited in anaerobic conditions while lysozyme release and phagocytosis were equally efficient in both aerobic and anaerobic conditions. All cell types tested were capable of intracellular killing of C. albicans and this appeared to be maximum at 6 h for monocytes and macrophages and 24 h for PMN. Monocytes killed the lowest number of organisms, 1 x 10(6), and the killing was similar for aerobic and anaerobic conditions. In contrast, PMN and macrophages demonstrated greater killing of C. albicans in aerobic conditions compared with anaerobic conditions; PMN killed 1.9 x 10(6) organisms and macrophages 3 x 10(6) when incubated anaerobically. Inhibitors of oxygen metabolism decreased intracellular killing of C. albicans by macrophages and PMN in aerobic but not anaerobic conditions. The oxygen reaction products involved in the killing of C. albicans appeared to be different however: macrophage killing was decreased by superoxide anion and hydrogen peroxide inhibitors. PMN killing was decreased by superoxide anion, hydrogen peroxide, hypochlorous acid and hydroxyl radical inhibitors. The present study shows that although monocytes, macrophages and PMN function similarly in their interaction with C. albicans, they appear to use different oxygen reactive products for the intracellular killing of C. albicans.